SOURCES OF POLITICAL INFORMATION AMONG YOUNG WOMEN IN PERAK - Boyman, Siti Noranizahhafizah; Jawan, Jayum; Besar, Junaidi Awang; Suhaili, Samsudin (International Journal of Psychosocial Rehabilitation, 2020)
This article examines trends in the preference for political information sources among young women in Perak. Media is one main sources for political information. Based on the growing number of youths from 10.8 million in 2005 (41 % of Malaysia's population) to 13.4 million in 2010, the influence of youth in determining change can be significant. In Perak youth accounted for about 37 % of the total voters in the 2013 general elections. This study seeks to identify the preference of media sources for political information among young women in Perak. The analysis will also determine the confidence level of political information source and issues that are important to them. Survey method is used and data will be processed thought a quantitative approach. A sample size of 450 young women were randomly selected. The results show that mainstream media played an important role as the main source of political information among the young women in Perak as compared to alternative medias. Television was the most important source of political information for them. In addition, respondents' confidence in the source of political information which they obtain from television was preceded by Astro Awani with the highest mean scores, followed by government-owned television stations, namely TV1 and TV2. With respect to print media newspapers like Berita Harian, Utusan Malaysia and The Star have the young women's confidence as compared to Keadilan Daily. It can also be said that young women do not choose alternative media as the media for political information because social media is widely being used to spread false information, which are often provocative and seditious. The study also found that current issues that affect young women's life were more important to young woman respondents, such as cost of living and educational issues.